Firm capabilities, technological dynamism and the internationalisation of innovation: A behavioural approach - Schubert, Torben; Baier, Elisabeth; Rammer, Christian (Journal of International Business Studies, 2018)
We develop a behavioural framework of bounded rational decision-making under uncertainty to analyse the role of technological dynamism in the firm’s environment for its decision to internationalise innovation. Applying prospect theory, we argue that technological uncertainty in the firm’s environment affects its risk preferences differently depending on its technological capabilities. A key prediction is that firms with low capabilities will internationalise innovation when faced by technological uncertainty while firms with high capabilities will concentrate their innovation at the home-base. We also argue that our behavioural approach based on prospect theory is not a stand-alone programme but benefits from the integration with traditional concepts in IB. In particular, we make a case that organisational measures fostering absorptive capacity, such as intensive personnel exchange between headquarters and subsidiaries, can help to attenuate the high-capability firms’ tendency to concentrate innovation at the home-base when faced by high uncertainty. We corroborate the predictions of our framework based on data from the German part of the Community Innovation Survey.